A syndemic of psychosocial health problems is associated with increased HIV sexual risk among Nigerian gay, bisexual, and other men who have sex with men (GBMSM). Issue 3 (3rd March 2020) - Ogunbajo, Adedotun; Oke, Temitope; Jin, Harry; Rashidi, William; Iwuagwu, Stella; Harper, Gary W.; Biello, Katie B.; Mimiaga, Matthew J.
ABSTRACT: Nigerian gay, bisexual and other men who have sex with men (GBMSM) experience negative psychosocial health problems, which may increase their risk for HIV infection. Few studies have explored the syndemic effect of co-occurring psychosocial health problems on HIV sexual risk among Nigerian GBMSM. We investigated the co-occurrence of syndemic psychosocial health problems and their synergistic effect on HIV risk behaviors. We assessed depressive symptoms, post-traumatic stress disorder, alcohol dependence, tobacco use, and hard-drug use. The outcome variables were the number of male sexual partners and consistent condom use. In a multivariable model, experiencing 4 or more psychosocial health problems – compared to experience none or one psychosocial health problem – was significantly associated with increasing number of male sexual partners. We found no statistically significant association between the number of syndemic psychosocial health problems and consistent condom use. Our study findings provides evidence of a synergistic relationship between negative psychosocial health factors and HIV sexual risk behavior. These findings underscore the importance of developing HIV prevention programming aimed at reducing HIV transmission risk that incorporate substance use and mental health treatments, in order to improve the overall health and quality of life for Nigerian GBMSM.